Evolution and Attribution Analysis of Habitat Quality in China’s First Batch of National Parks - Pengyue Dai; Yanfang Wang; Jinhong Ye; Jing Chen; Runze Li; Xiping Cheng (Land)
In October 2021, China established its first group of national parks, representing a milestone in enhancing the country’s nature reserve system and aligning with global trends in ecological conservation. This study aims to assess habitat quality changes and identify the driving factors in five national parks using multi-temporal land use data from 2000 to 2020. By integrating the land use transfer matrix with the InVEST model, we quantified habitat quality changes, while the geographical detector method was employed to analyze the key natural and socioeconomic drivers. Results showed that grassland and cultivated land were predominantly converted into forestland, leading to improvements in habitat quality in some parks. Specifically, Wuyishan National Park exhibited the highest and most stable habitat quality index, while Three-River-Source National Park experienced significant improvement (+34.10%). However, the Giant Panda, Northeast China Tiger and Leopard, and Hainan Tropical Rainforest National Parks experienced habitat degradation, with decreases of 15.15%, 14.50%, and 13.90%, respectively. Key drivers, such as NDVI, temperature, precipitation, elevation, and population density, were found to significantly influence habitat quality across the parks. This study highlights the ecological benefits of forestland restoration and the risks posed by the conversion of forest to cultivated or construction land, providing valuable insights for optimizing conservation strategies in China’s national parks.